Regulación emocional y síndrome de Burnout en guardas de seguridad de la ciudad de Tunja (2022)
The present research work aims to determine the relationship between Emotional Regulation and Burnout Syndrome in security guards in the city of Tunja, since it is a fundamental problem that is currently affecting the mental health of workers.